Design and evaluation of an ethnomathematics-based project-based learning model for enhancing students’ numeracy literacy and mathematical problem-solving in the society 5.0 era - Christa Voni Roulina Sinaga; Apriani Sijabat; Nelly Suka Sihite; Novia Carla Purba; Herna Febrianty Sianipar (Journal of Advanced Sciences and Mathematics Education, 2026)
Background: The rapid advancement of digital technology in the Society 5.0 era requires university students to possess strong numeracy literacy and mathematical problem-solving skills to interpret data, solve contextual problems, and make informed decisions. However, many students still experience difficulties in applying abstract mathematical concepts to real-life situations. This condition highlights the need for innovative and contextual learning approaches. Integrating ethnomathematics with Project-Based Learning (PjBL) offers a meaningful strategy to connect mathematical concepts with students’ cultural experiences. Aims: This study aims to design and evaluate an ethnomathematics-based PjBL model to improve university students’ numeracy literacy and mathematical problem-solving skills. Method: A quasi-experimental design with a pretest–posttest approach was employed. The participants were undergraduate students enrolled in a mathematics-related course. Data were collected through numeracy literacy tests, observation sheets, and project-based assessments. Students developed projects integrating mathematical concepts with local cultural contexts. Data were analyzed using descriptive and inferential statistics. Results: The findings indicated a significant improvement in students’ numeracy literacy and problem-solving abilities. Students showed better skills in interpreting data, solving contextual problems, and communicating mathematical reasoning. Cultural integration also increased engagement and motivation. Conclusion: The ethnomathematics-based PjBL model is effective in enhancing students’ numeracy literacy and supports innovative learning in the Society 5.0 era.